Evaluation of Enterococcus hirae isolated from vegetable wastes as probiotic and improvement of immune response in African catfish (Clarias spp.) - Hamid, Nur Hidayahanum (2022)
Disease outbreaks caused by the increased of aquaculture activities resulted in development of antibiotic-resistant bacteria. Therefore, probiotics usage as an alternative strategy has been suggested to be used as substitution for antimicrobial drugs. Lactic acid bacteria (LAB) constitute a group of Grampositive bacteria with high ability to produce antimicrobial compounds and improve fish performance which makes them excellent probiotics. Hence, the main objective for the study was to evaluate a bacterium, Enterococcus hirae isolated from vegetable wastes for growth promotion, immune responses and protection against Aeromonas hydrophila in juvenile catfish (Clarias spp.). Firstly, samples of vegetable wastes were divided into two groups (i.e. fermented and non-fermented wastes) and dried to determine the proximate composition according to Association of Official Analytical Chemists (AOAC, 1995) with some modifications. At the same time, wet samples were used to determine the pH and viable bacteria count. Isolation of LABs were done by using serial dilutions and plated onto deMan, Rogosa and Sharpe agar (MRSA) and incubated at 37°C. A 24 hr-old bacterial culture was used for primary identification of the isolates (through colony and cell morphology, and biochemical tests). Antagonistic tests were done in order to choose the isolates that could inhibit the growth of pathogenic bacteria. The selected isolates were then undergone haemolysis test using sheep blood agar. The selected isolates were identified by using commercial bacteria identification kit [API 20 STREP (Bio Mérieux, France)] and molecular techniques (16S rRNA and whole genome shot-gun sequences). Two isolates were chosen and designated as E. hirae UPM01 and UPM02. They were then were put through several additional tests to assess their properties as a probiotic candidate. The tests included the viability and growth at different pH (2-9), bile salt concentrations (0-0.3%), NaCl concentrations (0-7.5%) and temperature variation (5-55°C) using MRS broth; shelf-life storage at 4°C using normal saline; adhesion test with co-cultivation with bacteria pathogens and also antibiotic sensitivity test. After confirming their performances through these tests, both strains were selected for in vivo experiment in clariid catfish (Clarias spp.). The first feeding trial was conducted at the Laboratory of Aquatic Animal Health Unit, Faculty of Veterinary Medicine, Universiti Putra Malaysia. A total of 270 naive African catfish fingerlings were randomly divided into three groups [Control; group supplemented with Enterococcus hirae at 1×105 CFU/g feed (E1); and group supplemented at 1×107 CFU/g feed (E2)]. The feeding trials were conducted in 300-L fiber glass tanks each containing 200 litres of freshwater with 30 fish per tank. Tanks setup were arranged as a completely randomized design (CDR) with three replicates. All experimental fish were fed to satiation twice daily (09:00 hr and 15:00 hr) for 50 days. After 50 days, the experimental fish were checked for their growth rate, immune responses and survival test against A. hydrophila. The second feeding trial were conducted at the laboratory of Laboratory Aquatic Animal Health Management, Department of Aquaculture, Faculty of Fisheries, Kasetsart University, Thailand. A total of 450 hybrid naive clariid catfish fingerlings were randomly divided into three groups [Control; group supplemented with Enterococcus hirae at 2×105 CFU/g feed (E2C6); group supplemented at 2×107 CFU/g feed (E2C8)]. The feeding trials were conducted in 250-L fiber glass tanks containing 200 litres of freshwater with 30 fish per tank. Tanks set-up were arranged in a completely randomized (CDR) design with five replicates. All experimental fish were fed to satiation two times daily (09:00 hr and 15:00 hr) for 120 days. After 120 days, the experimental fish were analysed for their growth rate, immune responses and survival test against A. hydrophila. In the current study, nutrient analysis of vegetable wastes showed that fermentation of vegetable wastes not only resulted in reduction and slightly altered some nutritional parameters (dry matter and ash, crude proteins, crude fats and crude fiber), but also caused significantly (p<0.05) low pH value (increased in acidity) compared to the non-fermented samples. Additionally, the results obtained had shown that the number of microorganisms were significantly (p<0.05) abundant especially in the fermented samples. In the present study, 17 pure isolates from vegetable wastes (12 isolates from fermented samples and five isolates from non-fermented samples) were obtained from de Man Rogosa and Sharp (MRS) agar cultures. According to the antagonistic plate tests against A. hydrophila and Streptococcus agalactiae as aquatic pathogens, two LABs i.e. one from fermented cucumber waste and one from fermented mung bean sprouts wastes that showed the greatest inhibition zone were selected. The selected LABs were identified as E. hirae (later named as E. hirae UPM01 and UPM02). Probiotic properties evaluation of both E. hirae showed that they could survived at pH 2 up to 9 (p<0.05). Both E. hirae strains were active at different levels of NaCl (0 to 6.5%) and also, at various temperatures ranging from 5 to 45°C, but no growth at 55°C. The antibiotic sensitivity test showed that both strains were sensitive towards several antibiotics. The optimum duration of shelflife of both E. hirae in normal saline (0.85% NaCl) was considered not more than 20 days when stored at 4°C. In addition, a significantly (p<0.05) lower pathogenic bacteria population (A. hydrophila and S. agalactiae) were observed for the adhesion and co-culture test with E. hirae on the stainless-steel plates indicated that both strains were able to inhibit and compete with the both pathogenic bacteria for the site attachment. Moreover, the viability of both strains in prepared feed with initial concentration at 107 CFU/g at 15ºC for four weeks of storage were significant (p<0.05) but decreased in parallel to the duration of storage. It is suggested that the feed is best used within a week. The excellent survivability during 50 days of experimental period proposed that both E. hirae were nonpathogenic and did not have any negative effects on all experimental fishes. The concentration of 107 CFU/g feed of E. hirae supplemented feed as probiotic had positive effects on growth, average daily gain, feed conversion ratio and specific growth rate in juvenile African catfish, and the value was slightly better in UPM02, although no significant (p>0.05) was seen between the supplemented groups. Based on the current study, there was no significant (p>0.05) difference among experimental fishes including the control, in the histological assessment of intestine. However, from statistical analysis, the length of microvilli indicated that there was a significant (p<0.05) different between supplemented and control groups. In addition, supplementation of E. hirae also significantly (p<0.05) contributed to the enhancement of haematological parameters in juvenile African catfish during pre- and post-challenged period with A. hydrophila. The potential of E. hirae UPM02 was further investigated in juvenile hybrid catfish for longterm feeding experiment (120 days). In general, supplementation of diet at 2×107 CFU/g feed showed a low ability to improve growth performances of the experimental fishes. The supplementation at concentration of 2×105 CFU/g feed had more positive effects on the growth and feed utilization for hybrid catfish even though no notable differences (p>0.05) were found between both concentrations. In addition, the results of this study clearly indicated that the dietary supplementation of E. hirae at 2×105 CFU/g and 2×107 CFU/g of feed also significantly (p<0.05) enhanced the immune response and disease resistance of hybrid catfish against A. hydrophila compared to the control group fed with basal diet. Not only that, dietary E. hirae at both concentrations significantly (p<0.05) increased the expression level of the alpha-2- macroglobulin (α2M), CC chemokine, CXC chemokine, lysozyme C (LYZC), myeloperoxidase (MYE), NF-kappa-B1 p105 subunit (NF-K) and bactericidal permeability-increasing protein (BPIP) genes in head kidney, liver and spleen. At the same time, heat shock protein 70 (HSP70) gene expression was slightly down-regulated in those organs. In conclusion, to the best of our knowledge, the results from this study had demonstrated that E. hirae as a potential probiont for aquaculture for the first time